Investigation of Antibacterial and Cytotoxic Effects of Organic Acids Including Ascorbic Acid, Lactic Acid and Acetic Acids on Mammalian Cells - (:unkn) unknown (MEDWELL ONLINE, 2008)
Organic acids are becoming more accepted as substitutes for antibiotics. The aim of this study was to determine the antibacterial effects of ascorbic acid, lactic acid and acetic acid and at the same time to analyze the cytotoxicity of these organic acids to mammalian cells. The antibacterial effects of ascorbic acid, lactic acid and acetic acid in Brain Heart Infusion (BHI), at 4, 1, 0.5, 0.25 and 0.1% concentrations, on the bacteria suspensions of Staphylococcus aureus ATCC29740 and Escherichia coli DH5a strains, were determined by dilution methods. The cytotoxic effects of organic acids in Dulbecco's Modified Eagle's Medium (DMEM) at 4, 1, 0.5, 0.25 and 0.1% concentrations on cell cultures of murine fibroblast NIH 3T3 cells, were analyzed by the 3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) test. Antibacterial study showed that acetic acid was the most effective acid on both bacterial strains followed by lactic acid and ascorbic acid. Interestingly, although lactic acid was highly antibacterial, it produced the least cytotoxic effect on murine fibroblast cells. Acetic acid produced the strongest cytotoxic effect. At the same concentrations, the lowest pH values were measured in lactic acid containing media. It was followed by acetic acid. This study showed that the antibacterial and cytotoxic effects of organic acids may follow different mechanisms, on the other hand, pH changes caused by organic acids are not the only determining factor. Therefore, testing the cytotoxicity of organic acids on mammalian cells is usefull in preventing the detrimental effects of organic acids to the mammalian cells before using them as antibacterial agents.
Keywords: Antibacterial; cytotoxicity; ascorbic acid; lactic acid; acetic acid; FERMENTATION ACIDS; WEANED PIGS; PH; GROWTH